2016
DOI: 10.5414/cp202565
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the safety, pharmacokinetics, pharmacodynamics, and drug-drug interaction potential of GSK2647544 in healthy volunteers

Abstract: Abstract. Objective: To evaluate in healthy volunteers the safety, pharmacokinetics (PK), pharmacodynamics (PD), and drug-drug interaction (DDI) potential of GSK2647544, (a selective lipoprotein-associated phospholipase A2 (Lp-PLA2) inhibitor). Methods: Study 1 was a single-blind, randomized, placebo-controlled, crossover study with healthy male volunteers randomized to receive single escalating oral doses (0.5 – 750 mg) of GSK2647544. Study 2 was a single-blind, randomized, placebo-controlled study with healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…GSK2647544 has been evaluated as for the safety, tolerability, pharmacokinetics and pharmacodynamics in healthy volunteers in phase 1 clinical trials [123]. The compound was generally well tolerated and had a reasonable PK-PD profile [124]. In order to refine therapeutic dose predictions and confirm brain penetration, a radiolabelled form of the inhibitor [ 18 F]GSK2647544 was manufactured for use in a PET biodistribution phase Ι study [125].…”
Section: Inhibitors Of Lipoprotein-associated Phospholipase Amentioning
confidence: 99%
“…GSK2647544 has been evaluated as for the safety, tolerability, pharmacokinetics and pharmacodynamics in healthy volunteers in phase 1 clinical trials [123]. The compound was generally well tolerated and had a reasonable PK-PD profile [124]. In order to refine therapeutic dose predictions and confirm brain penetration, a radiolabelled form of the inhibitor [ 18 F]GSK2647544 was manufactured for use in a PET biodistribution phase Ι study [125].…”
Section: Inhibitors Of Lipoprotein-associated Phospholipase Amentioning
confidence: 99%
“…In the past few years, our group reported two series of novel Lp‐PLA2 inhibitors based on the pyrimidone scaffold, with a favorable selective inhibition toward Lp‐PLA2. Previous studies revealed that GSK2647544 had an improved PK profile compared with darapladib in human subjects . Indeed, we detected greater plasma exposure of GSK2647544 than that of darapladib when dosed orally to SD rats (GSK2647544: C max , 0.78 μg/mL; AUC (0‐∞) , 3.38 μg·h/mL at 25 mg/kg and darapladib: C max , 0.15 μg/mL; AUC (0‐∞) , 2.11 μg·h/mL at 50 mg/kg).…”
Section: Identification Of Small‐molecule Inhibitors Of Lp‐pla2mentioning
confidence: 72%
“…Remarkably, oral single doses of 125 mg GSK2647544 resulted in improved PK performance compared with single doses of 160 mg darapladib (area under curve [AUC] (0‐∞) : 2506 ng·h/mL of GSK2647544 vs 645 ng·h/mL of darapladib, ng·h/mL; C max : 457 ng/mL of GSK2647544 vs 18 ng/mL of darapladib, ng/mL). In addition, the inhibition of plasma Lp‐PLA2 activity was dose‐dependent, and 80 mg twice per day (160 mg daily dose) inhibited greater than or equal to 80% of plasma Lp‐PLA2 activity at trough, which is necessary for an enzyme inhibitor to produce a clinical effect . Furthermore, GSK2647544 could likely penetrate into the brains of preclinical species, which was verified by positron emission tomography biodistribution studies using [ 18 F] radiolabeled GSK2647544.…”
Section: Identification Of Small‐molecule Inhibitors Of Lp‐pla2mentioning
confidence: 85%
See 2 more Smart Citations